Excessiveness in a German Social Media Debate on Gender-fair Language - Acke, Hanna (Neuphilologische Mitteilungen, 2023)
Gender-fair language is a contested topic in contemporary Germany. Many reports on the introduction of language changes meant to reduce discrimination result in heated debates in print, online and social media. In this article, I qualitatively analyse a selected debate on gender-fair language on Twitter to find out how excessive the language use is and who makes use of what kind of excessive language. The time frame of analysis covers a critical discourse moment in 2018 during which the Council for German Orthography for the first time dealt with new gen- der-fair spelling variants. Since the Council, being the only official lan- guage planning institution for German, publishes the official regulations on orthography valid in schools and administrative bodies in Germany, its decision was highly anticipated and disputed. The analysed debate contained only a few argumentative exchanges on the topic. In general, it can be said that Twitter was mostly used to take a stance, not to engage in discussions. The overall style of the debate was polemic and exhibited many and various instances of excessive language use, mostly by opponents of gender-fair language. This group made use of vulgar language, pejoratives and in some cases direct insults. They especially questioned their adversaries’ mental health. Only a few pro- ponents used excessive language when they insinuated a lack of mental capacity in their adversaries.